Evidence for spatial coherence in time trends of marine life history traits of Atlantic salmon in the North Atlantic. Issue 2 (19th December 2018) - Olmos, Maxime; Massiot‐Granier, Félix; Prévost, Etienne; Chaput, Gérald; Bradbury, Ian R; Nevoux, Marie; Rivot, Etienne
Abstract: A hierarchical Bayesian life cycle model is presented that considers spatial covariation of marine life history traits of Atlantic salmon ( Salmo salar ) populations in the North Atlantic. The model is based on a collective analysis of the dynamics of 13 stock units (SUs) from two continental stock groups (CSGs) in North America and Southern Europe in a single hierarchical model over the period 1971–2014. The model sets up a new assessment framework for Atlantic salmon stocks. It also provides a framework to investigate the drivers of changes in Atlantic salmon population dynamics including disentangling the effects of fisheries from those of environmental factors in a hierarchy of spatial scales. It is used to test the hypothesis of a strong spatial synchrony in marine life history dynamics of Atlantic salmon populations. The trends in two key parameters associated with the early marine phase of the life cycle are estimated: (i) the marine survival during the first summer–autumn spent at sea and (ii) the proportion of fish maturing after the first winter at sea. The results provide evidence of a decline in the marine survival together with an increase in the proportion of fish that mature after the first winter at sea, common to all SUs. Our results show an increased coherence in the covariations of trends in these two marine life history traits related to geographic proximity of SUs which support the hypothesis of a coherent response of geographically proximate Atlantic salmon populations that likely share similar migration routes.